Cigarette smoking decreases TGF-β1 serum concentrations after long bone fracture - Moghaddam-Alvandi, Arash; Weiss, Stefan; Wölfl, Christoph Georg; Schmeckenbecher, Kerstin Helene Karin; Wentzensen, Andreas; Grützner, Paul Alfred; Zimmermann, Gerald (Injury, 2010)
TGF-β1 serum concentrations are considered to be one of the most promising markers of fracture healing. Previously, we demonstrated significant differences in the post-traumatic time courses of patients with timely and delayed fracture healing. The aim of this study was to evaluate possible differences in the serum concentrations of TGF-β1 in cigarette-smoking vs. non-smoking patients with timely and delayed fracture healing in order to understand pathophysiological pathways through which smoking impairs fracture healing. Serum samples were collected from 248 patients undergoing surgical treatment for long bone fractures within 1 year of surgery. Samples from 14 patients with atrophic-type delayed fracture healing were compared with 14 matched patients with normal bone healing. Each group included seven smokers and seven non-smokers. Post-operative serum concentrations were analysed at 1, 2, 4, 8, and 12 weeks as well as 1 year after surgery. The patients were monitored both clinically and radiologically for the entire duration of the study. All patients increased TGF-β1 serum concentrations after surgery. In patients with normal fracture healing, significantly higher TGF-β1 levels were observed in non-smokers (70ng/ml) than in smokers (50ng/ml) at the 4th week after surgery (p=0.007). Also at the 4th week, in patients with delayed healing, significantly lower TGF-β1 levels were observed in smokers than in non-smokers (38ng/ml vs. 47ng/ml, p=0.021). However, no significant differences between non-smokers with delayed healing and smokers with normal healing (p=0.151) were observed at the 4th week after surgery. TGF-β1 serum concentrations reached a plateau in all groups from the 6th to the 12th week after surgery, with a slight decrease observed in the final measurement taken 1 year after surgery. This study demonstrates that, after fracture, TGF-β1 serum concentrations are reduced by smoking, and this reduction is statistically significant during the 4th week after surgery. Our findings may help reveal the mechanism by which smoking impairs fracture healing. Furthermore, these results may help to establish a serological marker that predicts impaired fracture healing soon after the injury. Surgeons will not only be able to monitor the bone healing, but they will also be able to monitor the success of additional treatments such as ultrasound and bone morphologic proteins (BMPs).
Gesehen am 27.04.2023